2014
DOI: 10.3892/or.2014.3453
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β1-induced epithelial-mesenchymal transition in human esophageal squamous cell carcinoma via the PTEN/PI3K signaling pathway

Abstract: Epithelial-mesenchymal transition (EMT) is a crucial step for the invasive and metastatic properties of malignant tumor cells during tumor progression. Numerous signaling pathways are involved in the process of EMT in cancer, such as the EMT-inducing signal transforming growth factor (TGF)-β and the recently demonstrated PTEN/PI3K signaling pathway. To date, no data have been reported concerning the influence of PTEN/PI3K signaling pathway on EMT in human esophageal squamous cell carcinoma (ESCC) and how TGF-β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Here, we demonstrated that TGF-β1 induces changes in the morphology of ESCC cells and their transition from epithelial to mesenchymal phenotype. This change was shown to be accompanied by the downregulation of E-cadherin and upregulation of vimentin expression, which is consistent with the data obtained in the previous studies 12,13…”
Section: Discussionsupporting
confidence: 92%
“…Here, we demonstrated that TGF-β1 induces changes in the morphology of ESCC cells and their transition from epithelial to mesenchymal phenotype. This change was shown to be accompanied by the downregulation of E-cadherin and upregulation of vimentin expression, which is consistent with the data obtained in the previous studies 12,13…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have demonstrated that oncogenes, such as p53, c-Myc, matrix metallopepti- dase 9 and human sterile alpha motif domain-containing 9, are abnormally expressed in ESCC tissues (22)(23)(24). Furthermore, increased expression levels of transforming growth factor-β may stimulate the PTEN/PI3K pathway and promote epithelial-mesenchymal transition in the human esophageal epithelium (25). Epithelial-mesenchymal transition is a risk factor for ESCC, as cell junctions are disrupted and the invasive ability of ESCC is enhanced (26).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it promotes the growth, invasion, and metastasis of tumor by increasing synthesis of collagen in vascular endothelial cells. Besides, TGF-β1 can also affect epithelial-mesenchymal transition (EMT) and tumor growth by affecting PTEN-PI3K signal pathway [26]. The survival analysis shows that patients carrying TT genotype have got apparently a decrease in their recurrence-free survival time in comparison with patients carrying CC genotype.…”
Section: Discussionmentioning
confidence: 99%